Ceramide-Graphene Oxide Nanoparticles Enhance Cytotoxicity and Decrease HCC Xenograft Development: A Novel Approach for Targeted Cancer Therapy - Wang, Shi-Bing; Ma, Ying-Yu; Chen, Xiao-Yi; Zhao, Yuan-Yuan; Mou, Xiao-Zhou (Frontiers in Pharmacology, 2019)
Despite substantial efforts to develop novel therapeutic strategies for treating hepatocellular carcinoma (HCC), the effectiveness and specificity of available drugs still require further improvement. Previous work has shown that exogenous ceramide can play a key role in inducing the apoptotic death of cancer cells, however the poor water-solubility of this compound has hampered its use for cancer treatment. In the present study, we used polyethylene glycol (PEG) and polyethylenimine (PEI) co-conjugated ultra-small nano-GO (NGO-PEG-PEI) loaded with C6-ceramide (NGO-PEG-PEI/Cer) as a strategy for HCC treatment. We assessed the biological role of NGO-PEG-PEI/Cer, and we assessed its antitumor efficacy against HCC both in vitro and in vivo in combination with the chemotherapeutic drug sorafenib. We found that NGO-PEG-PEI significantly enhanced the cellular uptake of C6-ceramide. By investigating the mechanism of cellular delivery, we determined that the internalization of NGO-PEG-PEI/Cer progressed primarily via a clathrin-mediated mechanism. The combination of NGO-PEG-PEI/Cer and sorafenib exhibited synergy between these two drugs. Further work revealed that NGO-PEG-PEI/Cer may play a role in subverting multidrug resistance (MDR) in HCC cells by inactivating MDR and Akt signaling. NGO-PEG-PEI/Cer also significantly inhibited tumor growth and improved survival times in vivo, and the synergetic effect of NGO-PEG-PEI/Cer combined with sorafenib was also observed in drug-resistant HCC xenografts. In conclusion, our NGO-PEG-PEI nanocomposite is an effective nano-platform for loading C6-ceramide for therapeutic use in treating HCC, exhibiting high cancer cell killing potency in this tumor model. The NGO-PEG-PEI/Cer/sorafenib combination additionally represents a promising potential therapeutic strategy for the treatment of drug-resistant HCC.